2022
DOI: 10.1007/s11356-022-21805-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of removal efficiency of organic contaminant in landfill leachate-contaminated groundwater under micro-nano-bubble and common bubble aeration

Abstract: Land ll leachate contaminated groundwater is widespread all over the world. In order to study the organic contaminant removal e ciency of land ll leachate contaminated groundwater under oxygen micro-nanobubble (MNB) aeration, a series of lab-scale experiments of oxygen MNB aeration as well as common bubble (CB) aeration were conducted. On the one hand, the difference of mass transfer, microbial activity enhancement and contaminant removal e ciency between MNB and CB aeration were estimated. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Therefore, the DO concentration increased quickly and reached the maximum of 38.5 mg L −1 within 120 s. Then, the oxygen dissolution and overflow in groundwater reached equilibrium gradually with time, and the DO kept its peak value of 38.5 mg L −1 until the end of MNB aeration. According to Bai et al 39 and Hu and Xia, 40 the DO peak value in conventional oxygen aeration was about 8 mg L −1 . The high DO peak value indicated that MNB aeration effectively increased the DO concentration of groundwater.…”
Section: Mass Transfer In Mnb Aerationmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the DO concentration increased quickly and reached the maximum of 38.5 mg L −1 within 120 s. Then, the oxygen dissolution and overflow in groundwater reached equilibrium gradually with time, and the DO kept its peak value of 38.5 mg L −1 until the end of MNB aeration. According to Bai et al 39 and Hu and Xia, 40 the DO peak value in conventional oxygen aeration was about 8 mg L −1 . The high DO peak value indicated that MNB aeration effectively increased the DO concentration of groundwater.…”
Section: Mass Transfer In Mnb Aerationmentioning
confidence: 93%
“…Based on a previous study, 39 the preliminary energy consumption in MNB and conventional aeration were estimated. Specifically, in order to obtain the DO value of 8 mg L −1 in groundwater, oxygen MNB and conventional aeration lasted for 8 seconds and 5 minutes, respectively.…”
Section: Mass Transfer In Mnb Aerationmentioning
confidence: 99%
“…Over time, the technology and knowledge regarding nanobubbles (NBs) have continued to evolve and they are now gaining more and more applications, such as in water treatment [8], agriculture [9] and drug delivery [10]. Due to their unique properties, such as large specific area, high mass transfer efficiency and low rising velocity in liquid, nanobubbles have become popular research objects [11][12][13][14]. A model presented in [15] shows promising results for the use of cavitation to enhance heat transfer, as cavitation can thin the thermal boundary layer, reduce thermal resistance and improve heat transfer.…”
Section: Introductionmentioning
confidence: 99%